Adaptasi Mutu Pendidikan Islam Era Dinamis: Studi Kasus di Madrasah Tsanawiyah Sunan Ampel - Toyyibatul Mukminatus Sukriyah; Misbahul Arifin; Arini Nuora Darina; Tiara Nurul Annisa' (PARADIGMA: JURNAL PEMIKIRAN DAN PENELITIAN PENDIDIKAN, 2025)
This study focuses on the adaptation of Islamic education quality in response to the dynamic social, cultural, and technological changes of the modern era, using a case study at MTs Sunan Ampel Kamalkuning. The main objective is to analyze the quality development model implemented at the madrasah and to identify the supporting and inhibiting factors in the adaptation process. Employing a qualitative approach with a case study method, data were collected through observation, in-depth interviews, and documentation of various educational elements within the madrasah. The findings reveal that MTs Sunan Ampel Kamalkuning has successfully adapted its educational quality by integrating Islamic values with digital learning innovations, strengthening student character, and actively involving the community and parents. Transformational leadership by the principal and teacher collaboration emerged as key success factors in this development process. The madrasah has effectively responded to the challenges of the digital era while maintaining its Islamic identity and foundational values. The study implies that improving the quality of Islamic education requires a holistic approach that encompasses managerial, pedagogical, and spiritual aspects. These findings can serve as a reference for other Islamic educational institutions in formulating adaptive strategies amid rapid change, and open avenues for developing broader and more applicable quality models across diverse madrasah contexts in Indonesia.